(Z)-3-({[3-Methoxy-5-(trifluoromethyl)phenyl]imino}methyl)benzene-1,2-diol - Demir Kanmazalp, Sibel (Acta Crystallogr E Crystallogr Commun, 2019)
The title compound, C(15)H(12)F(3)NO(3), crystallizes with one molecule in the asymmetric unit. The mean planes of the two phenyl rings of the Schiff base moiety, bearing the OH groups and the imine group, respectively, are inclined to each other by 4.91 (1)°. In the crystal, molecules are linked via pairs of bifurcated O—H⋯O hydrogen bonds between the phenol OH groups, forming inversion dimers with an R (1) (2)(5) ring motif. The structure exhibits also intramolecular O—H⋯N and C—H⋯F hydrogen-bonding interactions. Hirshfeld surfaces analysis and two-dimensional fingerprint plots were applied to quantify the intermolecular interactions. The three F atoms of the trifluoromethyl group are disordered over two sets of sites, with occupancy factors of 0.578 (8) and 0.422 (8). The crystal studied was refined as an inversion twin